Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the quadratic equation [tex]\(x^2 - 14x + 58 = 0\)[/tex], we'll use the quadratic formula, which states that for any quadratic equation [tex]\(ax^2 + bx + c = 0\)[/tex], the solutions for [tex]\(x\)[/tex] are given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our specific equation [tex]\(x^2 - 14x + 58 = 0\)[/tex]:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = -14\)[/tex]
- [tex]\(c = 58\)[/tex]
First, calculate the discriminant, which is [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ b^2 - 4ac = (-14)^2 - 4 \cdot 1 \cdot 58 = 196 - 232 = -36 \][/tex]
Since the discriminant is negative, the solutions will be complex numbers.
Next, apply the quadratic formula:
[tex]\[ x = \frac{-(-14) \pm \sqrt{-36}}{2 \cdot 1} = \frac{14 \pm \sqrt{-36}}{2} = \frac{14 \pm 6i}{2} \][/tex]
This simplifies to:
[tex]\[ x = \frac{14}{2} \pm \frac{6i}{2} = 7 \pm 3i \][/tex]
Thus, the solutions are:
[tex]\[ x = 7 + 3i \quad \text{and} \quad x = 7 - 3i \][/tex]
Therefore, the correct answer is:
D. [tex]\(\{7+3i, 7-3i\}\)[/tex]
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our specific equation [tex]\(x^2 - 14x + 58 = 0\)[/tex]:
- [tex]\(a = 1\)[/tex]
- [tex]\(b = -14\)[/tex]
- [tex]\(c = 58\)[/tex]
First, calculate the discriminant, which is [tex]\(b^2 - 4ac\)[/tex]:
[tex]\[ b^2 - 4ac = (-14)^2 - 4 \cdot 1 \cdot 58 = 196 - 232 = -36 \][/tex]
Since the discriminant is negative, the solutions will be complex numbers.
Next, apply the quadratic formula:
[tex]\[ x = \frac{-(-14) \pm \sqrt{-36}}{2 \cdot 1} = \frac{14 \pm \sqrt{-36}}{2} = \frac{14 \pm 6i}{2} \][/tex]
This simplifies to:
[tex]\[ x = \frac{14}{2} \pm \frac{6i}{2} = 7 \pm 3i \][/tex]
Thus, the solutions are:
[tex]\[ x = 7 + 3i \quad \text{and} \quad x = 7 - 3i \][/tex]
Therefore, the correct answer is:
D. [tex]\(\{7+3i, 7-3i\}\)[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.